Demographic Compositions and Employment Issues of Urban Settlement Communities in Colombo District - Manel, D.P. Kanthi; Perera, Sunethra (My University, 2014)
Like in many other developing countries, Sri Lanka too urban work force contributes largely to the labour force of the country. Colombo is the highly urbanized district in the country whereas 78 percent of its population is currently living in urban areas. The informal sector absorbs approximately 45 percent of employment of the labour force, mainly to the non-agricultural employment (Department of Census and Statistics, 2012). Which is relatively high compared to other districts and it has also important impact on determining the low level of unemployment (3%) in the district. It is evident that all macroeconomic policies have direct and indirect effects on the growth of both urban informal and formal employment since 1970s. The number of people employed or unemployed or searching for work in an area depends primarily on the demographic compositions of its population. Also, demographic components such as births, deaths (natural increase) and migration determine the size and the age - sex structure of labour force. Previous studies have largely focused on economic aspects of urban informal sector and inadequately discussed the importance of demographic compositions and issues of current manpower. Therefore, this paper attempts to identify the demographic compositions and employment related issue in urban settlement context.
Keywords: Demographic Composition; Employment Participation; Urban Workforce